2009
DOI: 10.1152/ajplung.90587.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pleural mesothelial cell transformation into myofibroblasts and haptotactic migration in response to TGF-β1 in vitro

Abstract: Idiopathic pulmonary fibrosis (IPF) is a disease of unknown etiology characterized by the development of subpleural foci of myofibroblasts that contribute to the exuberant fibrosis noted in the pulmonary parenchyma. Pleural mesothelial cells (PMC) are metabolically dynamic cells that cover the lung and chest wall as a monolayer and are in intimate proximity to the underlying lung parenchyma. The precise role of PMC in the pathogenesis of pulmonary parenchymal fibrosis remains to be identified. Transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 46 publications
6
96
1
Order By: Relevance
“…TGF-b is most efficiently secreted as a large latent complex and most TGF-b is stored in the extracellular matrix before activation [19]. A key feature of IPF is the presence of high levels of inactive precursor form TGF-b1 in the lung parenchyma [27].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…TGF-b is most efficiently secreted as a large latent complex and most TGF-b is stored in the extracellular matrix before activation [19]. A key feature of IPF is the presence of high levels of inactive precursor form TGF-b1 in the lung parenchyma [27].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…However, our current understanding of DC chemotaxis is largely qualitative and limited to 2D (16)(17)(18)(19). Furthermore, while it is well established that cell migration requires different mechanisms in 3D vs. 2D (20)(21)(22)(23)(24)(25), nearly all chemotaxis studies to date have been performed in 2D or 2.5D conditions largely because of the lack of model systems in which well defined gradients can be created in 3D while evaluating cell invasion (especially because DC migration is relatively fast compared to the time scale of diffusion for gradient establishment).…”
mentioning
confidence: 99%
“…3 Nasreen et al 9 reported that TGF-b1 induces PMC EMT, and PMCs are a source of myofibroblasts in IPF. PMCs undergoing EMT produce large amount of collagen and contribute to the overdeposition of ECM in sub-pleural fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 PMCs with EMT are considered a source of myofibroblasts, which are the key cells within fibroproliferative foci. 3,8,9 Bleomycin is a classical inducer of pulmonary fibrosis model. In animal models, lung fibrosis induced by intraperitoneal bleomycin injection exhibits a sub-pleural fibrotic distribution similar to what is seen in human IPF.…”
Section: Introductionmentioning
confidence: 99%